2022
DOI: 10.1016/j.ejso.2022.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Fit4Surgery for cancer patients during covid-19 lockdown – A systematic review and meta-analysis

Abstract: Background Prehabilitation is a promising method to enhance postoperative recovery, especially in patients suffering from cancer. Particularly during times of social distancing, providing home-based programmes may have become a suitable solution to increase compliance and effectiveness. Methods In line with the PRISMA guidelines, a systematic review was conducted including trials that investigated the effect of home-based prehabilitation (HBP) in patients undergoing sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
(148 reference statements)
1
3
0
1
Order By: Relevance
“…29,30 This may even help optimize the outcomes of their surgery, which has been observed in surgical cancer patients and can be undertaken remotely. 31 MI, diabetes, and CTD were shown to be associated with approximately double the mortality risk during the first eight years following THA or KA, which is consistent with previous studies. 32,33 Two systematic reviews by Berstock et al 32,33 assessed mortality up to 90 days following THA or KA, and demonstrated a similar hazard ratio for mortality associated with comorbidities of diabetes and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…29,30 This may even help optimize the outcomes of their surgery, which has been observed in surgical cancer patients and can be undertaken remotely. 31 MI, diabetes, and CTD were shown to be associated with approximately double the mortality risk during the first eight years following THA or KA, which is consistent with previous studies. 32,33 Two systematic reviews by Berstock et al 32,33 assessed mortality up to 90 days following THA or KA, and demonstrated a similar hazard ratio for mortality associated with comorbidities of diabetes and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 91%
“… 29 , 30 This may even help optimize the outcomes of their surgery, which has been observed in surgical cancer patients and can be undertaken remotely. 31 …”
Section: Discussionmentioning
confidence: 99%
“…This will improvetheiroutcome,ashasbeenseeninpatientswithcancer whoareawaitingsurgery,andcanbeundertakenremotely. 45 This study has limitations. Comorbidities, joint-specific PROMs, and the progression of the radiological appearances were not assessed.…”
Section: Discussionmentioning
confidence: 92%
“…This will improve their outcome, as has been seen in patients with cancer who are awaiting surgery, and can be undertaken remotely. 45…”
Section: Discussionmentioning
confidence: 99%
“…Offen ist, wie ein Trainingsprotokoll für Patient*innen, die zum Training nicht in eine Klinik kommen können oder wollen, gestaltet sein sollte, z. B. als Heimtraining mit Unterstützung einer entsprechenden Applikation 34 . Künftige Studien müssen zudem evaluieren, wie passend das PRELS-Programm auch für Personen mit stärker eingeschränkter Funktionsfähigkeit ist.…”
Section: Diskussionunclassified